Cellular interference in craniofrontonasal syndrome: males mosaic for mutations in the X-linked EFNB1 gene are more severely affected than true hemizygotes. - Twigg, SR; Babbs, C; van den Elzen, M; Goriely, A; Taylor, S; McGowan, S; Giannoulatou, E; Lonie, L; Ragoussis, J; Sadighi Akha, E; Knight, S; Zechi-Ceide, R; et al. (Oxford University Press, 2013)
Craniofrontonasal syndrome (CFNS), an X-linked disorder caused by loss-of-function mutations of EFNB1, exhibits a paradoxical sex reversal in phenotypic severity: females characteristically have frontonasal dysplasia, craniosynostosis and additional minor malformations, but males are usually more mildly affected with hypertelorism as the only feature. X-inactivation is proposed to explain the more severe outcome in heterozygous females, as this leads to functional mosaicism for cells with differing expression of EPHRIN-B1, generating abnormal tissue boundaries-a process that cannot occur in hemizygous males. Apparently challenging this model, males occasionally present with a more severe female-like CFNS phenotype. We hypothesized that such individuals might be mosaic for EFNB1 mutations and investigated this possibility in multiple tissue samples from six sporadically presenting males. Using denaturing high performance liquid chromatography, massively parallel sequencing and multiplex-ligation-dependent probe amplification (MLPA) to increase sensitivity above standard dideoxy sequencing, we identified mosaic mutations of EFNB1 in all cases, comprising three missense changes, two gene deletions and a novel point mutation within the 5' untranslated region (UTR). Quantification by Pyrosequencing and MLPA demonstrated levels of mutant cells between 15 and 69%. The 5' UTR variant mutates the stop codon of a small upstream open reading frame that, using a dual-luciferase reporter construct, was demonstrated to exacerbate interference with translation of the wild-type protein. These results demonstrate a more severe outcome in mosaic than in constitutionally deficient males in an X-linked dominant disorder and provide further support for the cellular interference mechanism, normally related to X-inactivation in females.